The Sales Velocity Effect on Retailing. Issue 4 (November 2014) - Ho, Edward; Kowatsch, Tobias; Ilic, Alexander
In an increasingly crowded marketplace, retailers need innovative ways of promoting products to their consumers. E-commerce retailers have utilized to great effect lists of top ranked products to promote product sales; the higher the sales rank, the more likely consumers buy that product. This influence to buy, based on observing what others bought is known as observational learning (OL). Prior OL research assumed that OL arises from observing a static outcome, such as the current sales rank of a product. However, prior research on intertemporal choice showed that people prefer outcomes with increasing trends over stable or decreasing trends. This suggests that observing an increasing sales rank, denoted as sales velocity, would have a positive effect on purchase likelihood. We conducted three studies to test the sales velocity effect. Results show that sales velocity has a significant effect on likelihood of purchases, reversing even participant preferences for a product with a higher sales rank. This effect is consistent across four broad products tested. For researchers, by joining the two previously disparate branches of research in OL and intertemporal choice, we addressed a gap in OL research which previously ignored the velocity dimension of OL. For retailers, the study demonstrated the impact of the sales velocity metric on making choices, and thus they could use sales velocity data as a cost-effective marketing tool for specific products.